Correlates of Knowledge, Attitude and Practices about Health Care Waste Management among Hospital Workers of Pakistan - Kumar, Ramesh; Somrongthong, Ratana; Ahmed, Jamil; Almarabheh, Amer Jebril (Journal of Liaquat University of Medical & Health Sciences, 2019)
ABSTRACTBACKGROUND: Healthcare waste is considered as neglected public health problem in developing countries.OBJECTIVES: We aimed this study to explore the factors affecting the Knowledge, attitude and practices of health workers regarding healthcare waste management (HCWM) in Pakistan.METHODS: Cross sectional study was done in two major public-sector hospitals in Pakistan. Validated, pre-structured questionnaire used to interview 275 physicians, nurses and other auxiliary staff after taking written consent. The sample size was selected according to the proportional size of the each HCW after sample size calculation for their equal representation from all the healthcare workers groups.RESULTS: The responses to 24 questions for knowledge, 12 questions for attitude and 20 for practice were used to create three respective dependent variables for analysis to measure independent association of socio-demographic factors on the health workers’ knowledge, attitude and practice. Younger workers, males and paramedics were statistically significantly less likely to achieve mean score on knowledge and HCWM practices (P=<0.05). Operation theatres workers as compared to other departments were 25 times more knowledgeable and had better practices (P=<0.05). Paramedical staff was more knowledgeable and had better practices while handling the healthcare waste as compared to physicians and nursing staff (P=<0.001). Physicians had positive attitude as compare to paramedics and nursing staff (P=<0.001). Workers with 5-10 years of experience were 4 times more likely to have positive attitude about HCWM (P=<0.02). CONCLUSION: The occupation was statistically significant factors affecting the Knowledge, attitude and practices among doctors, paramedics and nurses.